Evaluasi Proses Bisnis Penanganan Pengaduan Nasabah Menggunakan Quality Evaluation Framework (QEF) (Studi Kasus : PT XYZ) - Iffa Aulia Ulwani; Nanang Yudi Setiawan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT XYZ is a company engaged in banking services. In handling complaints from customers, PT XYZ has a set of standards to maintain customers' trusts in using their services, namely the promptness of Service Level Agreement (SLA) in solving the problems that customers complain about. Unfortunately, SLA inaccuracy still occurs despite the small percentage. Thus, these problems need to be evaluated to measure the performance quality of the existing business processes and analyze whether there is a relevance to the evaluation results with the variation of business processes in PT XYZ. Business processes that have been modeled using petri net in YAWL are then simulated to generate the event log. Event logs are obtained by mining process in ProM tools using variant finder approach to determine the business process variation points. The QEF method is used to measure the gap between the objective of company and the quality of the existing business process. Then, we analyze the relevance of the evaluation results with the point of variabillity that appears. The result of this study shows that 5 points of variation and 3 factors that are not appropriate. Based on the results of calculations threre is no certain contribution with the variation of the evaluation results but can be the trigger of a new variation to reduce the number of nonconformities.